Cannabis-Based Therapies for Chronic Orofacial Pain: A Systematic Review and Meta-Analysis - Cruz Moreno , Tatiana (2026)
To evaluate the effectiveness of cannabis-based therapies in managing chronic pain associated with TMDs, periodontitis, and oral cancer. Chronic orofacial pain, especially in temporomandibular disorders (TMDs), presents a challenge in dental practice. Traditional treatments often have adverse effects and limited efficacy. Cannabis has emerged as a potential alternative due to its analgesic and anti-inflammatory properties. A systematic review and meta-analysis of randomized controlled trials, cohort, and case-control studies was conducted using five databases. Risk of bias was assessed using Cochrane ROB 2.0 and ROBINS-I tools. Six studies were included. Cannabis showed significant pain relief in oral cancer (OR=1.46; 95% CI: 1.24-1.71), while effects in TMDs and periodontitis were inconclusive. Cannabis may benefit oral cancer pain management; further studies are needed for TMDs and periodontitis.